The Green Deal and Carbon Footprint from Turkey’s Perspective: Is It a Threat? Is It an Opportunity? - Merve Ersoy Mirici; Süha Berberoğlu (Doğal Afetler ve Çevre Dergisi)
The relationship between economic growth on a global scale and absorption capacity of ecological capacity is possible to be seen in disaster and global climate change. The exemption of economy from ecological laws is a metabolic crack. Therefore, green quest remains relevant because country policies are changeable and global climate change mitigation strategies inch along. The green quest became a powerful weapon not only in the urban and rural landscape but also in economic transformation. The Green Deal as an extension of the Paris Agreement which came to the forefront as an anchor and discourse that aims at dissemination to all political areas of European Union’s (EU) environmental concern. The infrastructure of this discourse is the carbon footprint. The carbon footprint is a measure of the exclusive total amount of carbon dioxide emissions that are directly and indirectly caused by an activity or product. In this study, the place and position of the European Green Consensus in the reality of Turkey has been examined and the background of the carbon footprint, which constitutes the infrastructure of the Green Deal has been revealed. Confusions about carbon footprint calculating have been simplified and a holistic perspective. In this context, the relationship between consensus, pact and green areas, which stand out as green pursuits in EU countries, has been revealed in order to develop new and current perspectives within the scope of combating climate change in Turkey. The European Green Deal which is called the new green revolution can be assessed as a promising opportunity with regards to sustainable ecosystem resources and climate justice for next-generation although it seems like a threat at first glance for the Turkish economy.